Anticoagulation strategies in critical care for the treatment of atrial fibrillation: a protocol for a systematic review and meta-analysis. Issue 10 (20th October 2020) - Johnston, Brian; Nelson, Alexandra; Waite, Alicia C; Lemma, Gedeon; Welters, Ingeborg
Abstract : Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia in critically ill patients and is associated with an increased risk of thromboembolic events and mortality. Oral anticoagulation for thromboembolism prophylaxis is a key component of managing AF in the general population and is recommended by National Institute for Health and Care Excellence guidelines. However, assessment tools used to aid decision making about anticoagulation have not yet been validated in the critical care setting. There is a paucity of data assessing the impact of anticoagulation strategies on clinical outcomes in critically ill patients with AF. We present a protocol for a systematic review and meta-analysis to evaluate the effectiveness of anticoagulation strategies for AF used specifically in critical care. Methods and analysis: We will conduct a systematic review of the literature by searching MEDLINE, EMBASE, CENTRAL and PubMed databases for articles published from January 1990 to October 2019. Studies reporting anticoagulation strategies for AF in adults (>18 years) admitted to a general critical care setting will be assessed for inclusion. Outcomes of interest will include (1) percentage of patients started on anticoagulation in critical care for AF, (2) incidence of thromboembolism, (3) incidence of bleeding events, (4) intensive care unit (ICU) mortality, (5) hospital mortality, (6) ICU length of stay and (7) hospital length of stay. We will conduct a meta-analysis of trials. Risk of bias will be assessed using the Cochrane Risk of Bias tool for randomised trials or the Newcastle-Ottawa Risk of Bias assessment tool for non-randomised studies. This protocol and subsequent systematic review will be reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. Ethics and dissemination: This proposed systematic review will include data extracted from published studies; therefore, ethical approval is not required. The results of this review will be published in clinical specialty journals and presented at international meetings and conferences. Trial registration number: CRD42020158237.